Populism in Latin America : Second Edition - Conniff, Michael L. (Book collections on Project MUSE., 2012)
"This updated edition of Populism in Latin America discusses new developments in populism as a political phenomenon and the emergence of new populist political figures in Mexico, Argentina, and Venezuela in particular"--Provided by publisher